Sintesis dan Karakterisasi Hidrogel Superabsorben Kitosan Poli(N-Vinilkaprolaktam) (Pnvcl) Dengan Metode Full IPN (Interpenetrating Polymer Network) - Nadhrah Wivanius; Emil Budianto (Universitas Indonesia, 2015)
Polymer material used for hydrogel should have capability to swell and to keep water molecules in its structure without solubilised in water. Natural polymers has functional groups which can perform as active sites in modification to produce polymer with better characteristic. Chitosan is a natural polymer which has good swelling ability but lack of structural strength. Synthesis of chitosan hydrogel by interpenetrating polymer network (IPN) will increase its strength through crosslinking. In this research, the first step of modification was the synthesis of chitosan polymer network crosslinked by acetaldehyde. The next step was the synthesis of PNVCL polymer network crosslinked by N,N-methylbisacrylamide (MBA) through free radical polymerization of NVCL monomer with ammonium persulfat (APS) as the initiatior. Optimum reaction time, chitosan/PNVCL ratio (w/w %), concentration of crosslinker agent, and concentration of initiator had been observed. The optimum conditions were obtained as followed: 2 hours reaction, the ratio chitosan/PNVCL of 90:10 (w/w %), %-w MBA concentration of 0.5%, and APS concentration of 3%. The swelling ratio of the hydrogel was 380.66% while the crosslinking degree was 60.85%. Fourier transfor infrared spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), Thermogravimetric analysis (TGA), Scanning Electron Microscope (SEM), and X-Ray diffraction (XRD) were used for the characterization of the hydrogel.